Nephron-Sparing Surgery for Renal Masses Measuring Larger Than 7 cm on Preoperative Imaging: A Single Surgeon, Single Center Experience. (4th April 2013) - Esen, Tarık; Acar, Ömer; Musaoğlu, Ahmet; Vural, Metin; Akpek, Sergin
Abstract : Objectives . To document the feasibility of nephron-sparing surgery (NSS) for the surgical treatment of renal masses measuring larger than 7 cm (cT2) on preoperative imaging. Methods . A total of 139 patients have undergone NSS between 2001 and 2012 by a single surgeon in our clinic. Of these, we identified 17 patients whose tumors were measuring greater than 7 cm on preoperative imaging studies and were limited to the kidney. Their charts were retrospectively reviewed. Results . Mean age of the study population was 49.8 ± 11.3 years. Thirteen patients were managed by open NSS, while 4 patients have undergone robot-assisted NSS. Mean diameter and mean R.E.N.A.L. score of the tumors that were enucleoresected were 8.2 cm and 8.5, respectively. A total of 5 Clavien grade 2 and higher complications were recorded within 30 days of surgery. Histopathologic examination revealed benign histology in almost 1/4 of the cases. After a median followup of 33 months, all of our patients were alive. Only one patient (5.8%) experienced local recurrence. Conclusions . NSS is a feasible and safe option for large (>7 cm) renal masses. It may be considered not only for imperative conditions but also for highly selected cases with a normal contralateral kidney.